History of Educational Migration in Georgia: From Ancient Times to the Soviet Period - Shelia, Mzia; Tukhashvili, Mirian (Journal of Education Culture and Society, 2024)
Aim. The problem of “brain drain” is currently very relevant for Georgia. It is a fact that, despite the country’s low economic development, the number of people wishing to obtain higher education abroad has grown rapidly. This process often leads to permanent migration thus reducing the intellectual and labour potential of the country. Our goal was to find out whether this event also took place in Georgia in the historical past and how our ancestors managed it. Methods. The present work is based on historical documents, some of which were found by the author in the personal archives of Georgian scientists. Results. The research has revealed that educational migration is not new to Georgia. For thousands of years it has been both organised and unorganised in nature. It has been established that still in early 1900s, educational migration was studied in Georgia under the leadership of Prof. Ivane Javakhishvili. This allowed us to identify the geographical area and professional interests of those who went to study abroad. Conclusion. It was also established that against the backdrop of incessant wars that continued for hundreds of years, educational migration has contributed to the preservation of a more or less stable regime of social and cultural development of the country.